Analysis of Mutation Spectra of 28 Pathogenic Genes Associated With Congenital Hypothyroidism in the Chinese Han Population - Huang, Miao; Lu, Xiyan; Dong, Guoqing; Li, Jianxu; Chen, Chengcong; Yu, Qiuxia; Li, Mingzhu; Su, Yueyue (Frontiers in Endocrinology, 2021)
Purpose: Congenital hypothyroidism (CH) is the most common neonatal endocrine disease; its early detection ensures successful treatment and prevents complications. However, its molecular etiology remains unclear. Methods: We used second-generation sequencing to detect 28 pathogenic genes in 15 C h i n e s e Han patients with CH in Shenzhen, China, and analyzed the genetic pattern of the pathogenic genes through their pedigrees. The pathogenicity assessment of gene mutations was performed based on the American College of Medical Genetics and Genomics (ACMG) classification guidelines, inheritance models, and published evidence. Results: Mutations in several target genes were identified in 14 of 15 patients (93.33%); these mutations were distributed in eight genes (DUOX2, DUOXA2, TPO, TG, TSHR, FOXE1, KDM6A, and POU1F1). DUOX2 exhibited the highest mutation frequency (44%, 11/25), followed by TPO (16%, 4/25) and TG (16%, 4/25). DUOX2 exhibited the highest biallelic mutation (7/15). E i g h t o u t o f 25 variants verified by the ACMG guidelines were classified as pathogenic (P, category 1) or possibly pathogenic (LP, Type 2), namely six variants of DUOX2,andonevariant of TPOandDUOXA2. Five new mutations were detected:onein DUOX2, which was located in the splicing region of mRNA (c.1575-1G>A), three new missense mutants, p.A291T, p.R169W, and p. S1237dup, and one new TPO missense variant c.2012G>T (p.W671L). The main criteria for determining the genotype–phenotype relationship were a diagnostic detection rate of 53.33% (8/15) and combination of three or more gene mutations. Conclusions: CH gene mutations in the population may be mainly manifested in genes influencing thyroid hormone synthesis, such as DUOX2 compound heterozygous mutations, which exhibited a high detection rate. The clinical manifestations are diverse, and mainly include transient CH. Therefore, genetic screening is recommended for CH patients to determine the correlation between clinical phenotypes and gene mutations, which will assist in clinical management.